MODEL KEMITRAAN PEMBANGUNAN PEDESAAN DI KABUPATEN KOLAKA PROVINSI SULAWESI TENGGARA - Muchtar, La Ode Mustafa; Prajarto, Nunung; Subejo, dan (Agriekonomika, 2013)
ABSTRACTApproach model of local government in managing local development that has not been integrated so that the implementation of development programs so far has not fully realize a prosperous society in Kolaka regency. This research aims to describe the implementation of rural development, identify the factors inhibiting and driving the implementation of rural development, and describe the factors that determine the effectiveness of the implementation of rural development programs in Kolaka regency. The research design was a descriptive with qualitative approach. The results showed that the implementation of rural development programs through Gerbangmastra program entirely not maximized, because there are still obstacles that impede the achievement of objectives adequately. Public private partnerships, socialization of program development and community participation very determine the effectiveness of achieving objectives rural development through the implementation of Gerbangmastra programs. Public private partnership in the implementation of the program is not maximized, socialization of program uneven and community participation is still low, so the effectiveness of the achievement of development objectives through the implementation of Gerbangmastra program not maximized.Keywords:Â  public-private partnerships, socialization of program, community participation, development program, effectiveness. Â